2013
DOI: 10.1016/j.ajog.2012.11.033
|View full text |Cite
|
Sign up to set email alerts
|

Maternal psychosocial stress during pregnancy is associated with newborn leukocyte telomere length

Abstract: Objective In adults, one of the major determinants of leukocyte telomere length (LTL), a predictor of age-related diseases and mortality, is cumulative psychosocial stress exposure. More recently we reported that exposure to maternal psychosocial stress during intrauterine life is associated with LTL in young adulthood. The objective of the present study was to determine how early in life this effect of stress on LTL is apparent by quantifying the association of maternal psychosocial stress during pregnancy wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
140
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(156 citation statements)
references
References 65 publications
12
140
1
3
Order By: Relevance
“…14,15 New work has raised the possibility of fetal programming of telomere biology, whereby stress-related maternalplacental-fetal interactions during intrauterine growth regulate the initial setting of TL at birth. 6,16,17 Perceived facial age is an assessment of how old a person looks relative to his or her chronological age. The visual signs of aging (eg, skin wrinkles) reflect declining tissue integrity, indicative of the aging process.…”
mentioning
confidence: 99%
“…14,15 New work has raised the possibility of fetal programming of telomere biology, whereby stress-related maternalplacental-fetal interactions during intrauterine growth regulate the initial setting of TL at birth. 6,16,17 Perceived facial age is an assessment of how old a person looks relative to his or her chronological age. The visual signs of aging (eg, skin wrinkles) reflect declining tissue integrity, indicative of the aging process.…”
mentioning
confidence: 99%
“…In 2013, the same group conducted a study on 27 mother-newborn dyads in order to assess how early maternal stress levels during pregnancy (i.e. also prenatal) affect newborn leukocyte TL [67]. In this second study, the authors found further evidence for significantly shorter leukocyte TL in newborns from mothers with greater stress exposure, indicating some sort of stress-related programming reflected in newborn TL.…”
Section: Transference Of Stress-induced Psychopathologiesmentioning
confidence: 57%
“…36 Entringer et al 37 assessed leukocyte telomere length in cord blood peripheral cells and observed a significant, independent, linear effect of pregnancy-specific stress on newborn infant leukocyte telomere length. These findings indicate that psychologic stress during pregnancy may program the developing telomere biology system, which is 1 of the predictors of agerelated diseases and death.…”
Section: Ajogorgmentioning
confidence: 99%